Making photography matter : a viewer's history from the Civil War to the Great Depression - Finnegan, Cara A. (University of Illinois Press, 2015)
"Photography became a dominant medium in cultural life starting in the late nineteenth century. As it happened, viewers increasingly used their reations to photographs to comment on and debate public issues as vital as war, national identity, and citizenship"--Jacket